Factors Related To Stunting Prevention Practices At The Mersam Public Health Center, 2025 - Hoirunnisa Sabilah; M. Ridwan; Budi Aswin; Dwi Noerjoedianto; Ashar nuzulul putra (CV. AFDIFAL MAJU BERKAH, 2026)
Stunting remains an important public health problem because it affects children's growth and development. Mothers' behavior in preventing stunting is one of the key efforts to reduce the incidence of stunting among children under five. Several factors such as knowledge, attitudes, and family support are thought to be associated with stunting prevention behavior. This study aimed to determine the factors associated with stunting prevention behavior among mothers with children under five in the working area of Mersam Public Health Center, Batanghari Regency. The results showed that most respondents had good stunting prevention behavior (58.9%). The majority of respondents had good knowledge (62.2%), poor attitudes (75.6%), and good family support (64.4%). Bivariate analysis showed that knowledge was significantly associated with stunting prevention behavior (PR=1.73; 95% CI=1.07–2.82; p=0.045), and attitude was also significantly associated with stunting prevention behavior (PR=2.66; 95% CI=1.04–6.69; p=0.023). Meanwhile, family support was not significantly associated with stunting prevention behavior (PR=0.87; 95% CI=0.50–1.48; p=0.769).